The Use Of Canva as Media In Teaching Reading Comprehensions at Seventh Grade Students Of SMP Negeri Tiakur - Lakburlawal, Yulius Adelius; Lekawael, R. F. J.; Meyer, Fredi (Koli Journal : English Language Education, 2024)
The use of the Canva application as Media in teaching reading comprehension proves to be a beneficial tool for seventh-grade students at SMP Negeri Tiakur. The research aimed to investigate how effectively the Canva application could be implemented in the teaching and learning process of reading comprehension among these students. The study used classroom action research, which involved 25 seventh-grade students at SMP Negeri Tiakur and utilized both qualitative and quantitative (reading tests) data analysis methods. The research consisted of two cycles, each with two sessions. Initially, students achieved an average score of 70 % in their reading tests during cycle I, which significantly improved to 90 % above by cycle II, demonstrating substantial enhancement in their reading skills. The effectiveness of the Canva application in teaching reading comprehension is evident and recommended for use during class activities